THE BIOLOGY OF CANADIAN WEEDS.: 1. Kalmia angustifolia L. - HALL, IVAN V.; JACKSON, LLOYD P.; EVERETT, C. FRED (Canadian Journal of Plant Science, 1973)
This contribution on Kalmia angustifolia L., sheep-laurel (Ericaceae), is part of a series that presents biological information on plants that are weedy in Canada. Kalmia angustifolia is a weed of lowbush blueberry fields and pastures in eastern Canada. It occurs in Newfoundland, Prince Edward Island, Nova Scotia, New Brunswick, Quebec, and Ontario.